"Plates and Dishes Smash; Married Couples Clash": Cultural and Social Barriers to Help-Seeking Among Women Domestic Violence Survivors in Kyrgyzstan. (May 2018) - Childress, Saltanat
This article develops a grounded theory of help-seeking to investigate the social and cultural determinants of help-seeking among Kyrgyz women who have experienced domestic violence. Results indicate that cultural traditions and social norms—most notably the social construction of marriage, the shame associated with divorce, and the status of daughters-in-law in Kyrgyz society—are used to justify domestic violence and prevent victims from seeking help. The proposed theory and results suggest that scholars, policymakers, and front-line contacts must emphasize dispelling myths, misconceptions, and traditional beliefs about gender and marriage to break the abusive dynamics and provide professional help.